2004
DOI: 10.3171/jns.2004.101.1.0104
|View full text |Cite
|
Sign up to set email alerts
|

Improvement in neurological outcome after administration of atorvastatin following experimental intracerebral hemorrhage in rats

Abstract: Analysis of the data in this study indicates that atorvastatin improves neurological recovery after experimental ICH and may do so in part by increasing neuronal plasticity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
102
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 120 publications
(107 citation statements)
references
References 20 publications
5
102
0
Order By: Relevance
“…As an experimental model, the direct injection of autologous blood into the striatum in the rat has proven reliable for studying the pathophysiological changes occurring after spontaneous ICH (Seyfried et al, 2004). In the ICH model of injury we have demonstrated that MSCs localize around the ICH and that features of active neuroregeneration are present after intravenous administration of 3-8 million cells (Seyfried et al, 2006).…”
Section: Discussionmentioning
confidence: 87%
“…As an experimental model, the direct injection of autologous blood into the striatum in the rat has proven reliable for studying the pathophysiological changes occurring after spontaneous ICH (Seyfried et al, 2004). In the ICH model of injury we have demonstrated that MSCs localize around the ICH and that features of active neuroregeneration are present after intravenous administration of 3-8 million cells (Seyfried et al, 2006).…”
Section: Discussionmentioning
confidence: 87%
“…The promising neuroprotective benefit of the statins in acute ischemic stroke [125][126][127] has led to a similar evaluation in ICH models. In the autologous whole blood model, atorvastatin at 2 mg/kg was beneficial, and higher doses did not improve outcome or reduce the extent of injury [128]. Atorvastatin reduced perihematoma cell death via an anti-inflammatory mechanism and this was also associated with sensorimotor recovery [129].…”
Section: Anti-inflammatory Agents: Statinsmentioning
confidence: 97%
“…The neurological improvement became apparent at 1 week and was consistent throughout 4 weeks. In addition, the statins increased cell proliferation and differentiation suggesting that enhanced neuroplasticity may be the mechanism for improved function [128,130].…”
Section: Anti-inflammatory Agents: Statinsmentioning
confidence: 99%
See 1 more Smart Citation
“…The most compelling preclinical data is in experimental SAH, where statins have been demonstrated to reduce vasospasm and improve outcomes after SAH in the mouse, 39,60 rat, 61,62 rabbit, 39,63 and dog. 64 Similarly, statin treatment has been shown to improve outcomes in murine models of intracranial hemorrhage 65,66 and acute ischemic stroke. [67][68][69] …”
Section: Preclinical Models Of Acute Brain Injurymentioning
confidence: 99%